1996
DOI: 10.1021/la950968m
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Characterization of Sulfonated Aluminum Phthalocyanines in a Cationic Reversed Micellar System

Abstract: The photophysics of sulfonated aluminum phthalocyanines, AlPcSn (n ) 0, 1, 2, 3, or 4), in cationic reversed micelles of benzyldimethyl-n-hexadecylammonium chloride (BHDC) have been investigated. Absorption and steady-state fluorescence emission spectroscopy indicate that only the di-and trisulfonated derivatives are essentially monomeric. Consequently, the triplet-state properties of only these nonaggregated phthalocyanines were investigated. Both derivatives exhibited enhanced intersystem crossing in this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…Equation (2) is a modification of Gradyusho's equation, f f f t = 1 [19] and was modified by Gouterman [20]. The f t values appearing in Table 1 were calculated utilizing a f ic of 0.16 taken from Dhami et al [21] for an aluminum phthalocyanine disulfonate species in methanol. Much of the data seen in Table 1 was recently reported as part of a larger study involving phthalocyanine, porphyrin, benzochlorin, and purpurin photosensitizers [22].…”
Section: Photophysical Measurementsmentioning
confidence: 99%
“…Equation (2) is a modification of Gradyusho's equation, f f f t = 1 [19] and was modified by Gouterman [20]. The f t values appearing in Table 1 were calculated utilizing a f ic of 0.16 taken from Dhami et al [21] for an aluminum phthalocyanine disulfonate species in methanol. Much of the data seen in Table 1 was recently reported as part of a larger study involving phthalocyanine, porphyrin, benzochlorin, and purpurin photosensitizers [22].…”
Section: Photophysical Measurementsmentioning
confidence: 99%
“…75 It has been suggested that binding of tetrasulfonated metallophthalocyanines to phospholipid membranes is determined primarily by metal−phosphate coordination. 76 The hydrophilic or lipophilic property of the photosensitizers is related to their water solubility, which controls aggregation properties, and singlet oxygen production efficiency. Among the hydrophilic photosensitizers, anionic derivatives with sulfo substituents (Figure 1) such as AlPcS 4 are one of the best targets for a new generation of photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Studies have also demonstrated that a water-soluble tetrasubstituted cationic aluminum phthalocyanine (AlPcN(4)) efficiently bound to phospholipid membranes behaved similar to anionic tetrasulfonated aluminum and zinc phthalocyanine complexes. 22 Thus, the binding of tetrasulfonated metallophthalocyanines to phospholipid membranes has been suggested to be primarily determined through metal-phosphate coordination. 22 Among the hydrophilic photosensitizers, anionic derivatives of metal complexes of phthalocyanines with sulpho substituents, such as zinc tetrasulfonated phthalocyanine (ZnPcS 4 ) or AlPcS 4 , are some of the best targets for the generation of novel photosensitizers.…”
mentioning
confidence: 99%
“…22 Thus, the binding of tetrasulfonated metallophthalocyanines to phospholipid membranes has been suggested to be primarily determined through metal-phosphate coordination. 22 Among the hydrophilic photosensitizers, anionic derivatives of metal complexes of phthalocyanines with sulpho substituents, such as zinc tetrasulfonated phthalocyanine (ZnPcS 4 ) or AlPcS 4 , are some of the best targets for the generation of novel photosensitizers. Metal phthalocyanines have become popular in PDT since Ben-Hur 23 reported the anticancer properties of phthalocyanine aluminum chloride.…”
mentioning
confidence: 99%